The Relationship Between State and Society: Managing Poverty Through Local Wisdom - Sri Djoharwinarlin (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
State and society must support one another to manage the poverty in order to reach welfare. Society tries to fulfill basic needs by implementing their local wisdom. On the other hand, state supports the society by give facilities and access to preserve traditions and to adapt them to the dynamic era. Having Banyusoca, Pilangrejo, and Planjan as the location of study cases, this article points out that local wisdom is not only used to empower society but also used to manage poverty that has been an endless scourge.